2016
DOI: 10.3233/ch-152009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of histological subtypes of clear cell renal cell carcinoma using contrast-enhanced ultrasound (CEUS)

Abstract: Our study suggests that CEUS may be an additional tool for non-invasive characterisation and differentiation of the three histological subtypes of clear cell RCC. Furthermore, it seems to have an additional diagnostic value in daily clinical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…RCC is an abundant blood supply tumor with high density and thin-walled blood vessels, leading to an accelerated circulation of contrast medium and shortening perfusion and clearance. AML is characterized by malformed blood vessels, irregularly thickened walls, and narrow lumens, resulting in the slow circulation of the contrast agent and long perfusion and clearance (17,18,27). Dai et al (28) demonstrated that the peak intensity of a tumor (PI t ) and the time to peak intensity of a tumor (TTP t ) between benign and malignant lesions were both statistically significant (P=0.003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCC is an abundant blood supply tumor with high density and thin-walled blood vessels, leading to an accelerated circulation of contrast medium and shortening perfusion and clearance. AML is characterized by malformed blood vessels, irregularly thickened walls, and narrow lumens, resulting in the slow circulation of the contrast agent and long perfusion and clearance (17,18,27). Dai et al (28) demonstrated that the peak intensity of a tumor (PI t ) and the time to peak intensity of a tumor (TTP t ) between benign and malignant lesions were both statistically significant (P=0.003.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al (9) found that both centripetal enhancement in the cortical phase (71.9% vs. 23.2%) and homogeneous peak enhancement (100% vs. 27.5%) were important for differentiating an AML from a ccRCC. Some researchers have reported that ccRCC is mainly characterized by heterogeneous hyperperfusion, while pRCC and chRCC mostly feature homogeneous hypoperfusion (17,18). In our more recent study, it was found that hyperenhancement (64/81, 79.0%), homogeneous enhancement (54/81, 66.7%), fast wash-out (WO) (63/81, 77.8%), and peripheral rim-like enhancement (PRE) (45/81, 55.6%) were the typical features of small RCC (19).…”
Section: Introductionmentioning
confidence: 99%
“…During image fusion, it is still technically possible to use all other image modes of the ultrasound system, such as color Doppler and CEUS. Using all the different image techniques in real time allows comprehensive imaging and characterization of the vascularization of renal lesions [11,21-23]. Lesions that cannot be sufficiently seen on native B-mode ultrasound, for example due to a very deep location of the lesion, sometimes cannot be co-registered with the CT imaging dataset due to the normal limitations of conventional ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, ccRCC often shows early inhomogeneous enhancement and rapid regression. The enhancement margin around the lesion described as pseudocapsule is usually apparent in the late stage of regression, which is another characteristic manifestation of diagnostic ccRCC [ 13 ]. Conversely, pRCC usually shows progressive enhancement and persistent low enhancement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%